Rancang Bangun Jig and Fixture Pembengkok Pipa Baja Untuk Pembuatan Rangka Meja Kelas - Pardi Pardi; Erwanto Erwanto; Nanda Pranandita (Politeknik Manufaktur Negeri Bangka Belitung, 2026)
The process of bending steel pipes in making classroom table frames in many workshops is still carried out manually, resulting in less precise bending angles, inconsistent product quality, and low work efficiency. This study aims to design and make a jig and fixture for bending steel pipes as a tool to assist in the classroom table frame manufacturing process by applying the VDI 2222 method. The research stages include literature review, needs analysis, concept design, selection of design alternatives, making the tool, and testing the tool's performance. The testing was conducted on several types of steel pipes, namely galvanized pipes with thicknesses of 0.9 mm and 1.7 mm, as well as ST37 pipes with thicknesses of 1.4 mm and 1.7 mm. The results show that the designed jig and fixture can bend steel pipes up to a 90° angle while keeping the pipe stable during the bending process. The material and thickness of the pipe affect the quality of the bending results, where the thicker the pipe, the greater the force required and the higher the potential for wrinkles to form on the inside of the bend. A 1.4 mm thick ST37 steel pipe produces bending quality that is most suitable for making classroom table frames. Overall, the designed tool has fulfilled its function as a steel pipe bending aid, although further development is still needed on the forming and holding system to reduce bending defects and lower the operating force.